Population dynamics and fisheries assessment of the bigeye thresher (Alopias superciliosus) in the Atlantic: a comparison between North Atlantic and South Atlantic stocks - Carvalho, Joana Fernandez de (2014)
Tese de doutoramento, Ciências do Mar, da Terra e do Ambiente (Biologia Pesqueira), Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2015 The bigeye thresher shark, Alopias supercilious is an oceanic pelagic shark, occasionally caught as bycatch in pelagic longline fisheries targeting tunas and swordfish in the Atlantic Ocean. It is particularly vulnerable to fishing pressure, with overexploitation occurring even at low levels of fishing, due to their slow growth, extremely low fecundity and migratory nature crossing both national and international waters. The present study focused on several aspects of the biology and fisheries of this species, including fisheries impact, gear modification for bycatch mitigation, life history, distribution patterns and habitat utilization. The bigeye thresher was amongst the shark species with the highest hooking mortality rates (around 50%) by the Portuguese pelagic longline fleet. When testing possible gear modification to reduce the bycatch, the use of circle hooks or mackerel bait (instead of J-style hook and squid bait) does not seem to be an effective mitigation measure. Life history parameters, specifically age, growth and size at maturity were estimated, with the observed growth coefficients (k values) being the lowest ever presented for the species and within the Alopiidae family. Three nursery areas were proposed along the Atlantic Ocean, specifically in the tropical northeast Atlantic and equatorial waters closer to the African continent, in the tropical northwestern Atlantic in areas closer to the Caribbean Sea and Florida, and in the southwest Atlantic closer to the Rio Grande Rise. Finally, satellite telemetry was used to study habitat use and vertical migrations of this species, and when compared to the depth of operation of the longline fishing gear resulted that most of the overlaps between habitat and gear deployment occur during the night and seem to affect more the juveniles. The results presented in this thesis are being integrated into ...